Forecasting Final Cost and Time Rates of Highway Construction Projects in Iraq Using Regression Analysis - Dhuha M. Dawood; Abbas M. Abd; Raquim N. Zehawi (Diyala Journal of Engineering Sciences, 2023)
The construction process is fraught with risks and uncertainties, which grow in proportion to the size and complexity of the project. The project is considered successful if it is completed within the specified time and cost and with the required quality standards. The time and cost overrun of building projects and highways is a critical issue because of the great risks that result from it, which affect the project completion process and sometimes put it to a halt. In this paper, an attempt was made to predict the final cost rate and final time rate of such projects before starting work, using the technique of reverse elimination regression analysis.  The study covers a group of highway projects in Diyala Governorate, where the records of (25) projects that were completed during (2012-2021) were used to develop and validate the regression model.  Based on the experts' convictions, there are nine factors that are considered the most influential on the final cost and final time.  Hence they are used as input parameters for the form.  These factors are; bid cost, bid duration, change order cost, change order duration, final cost, and final duration, no. of change order, start time and final time. It was found that the developed regression model has the ability to predict the final cost rate (FCR) and final duration rate (FDR) for highway projects as outputs with very high  goodness of fit and coefficient determination ( ) of (98%) and  (96%) for FCR and FDR respective.